Faktor- Faktor yang Mempengaruhi Minat Siswa SMK Negeri 1 Bukittinggi Dalam Pemilihan Jurusan di Perguruan Tinggi - Dini Rahayu; Elviana Elviana (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Education is one way for individuals to explore their potential. Education is a necessity of human rights. Every individual has the right to receive education according to his wishes and needs. Interest in continuing education at tertiary institutions is of course the desire of every individual. So in this case it is necessary to study the factors that support students' interest in continuing higher education. In describing these factors, researchers used a qualitative approach with interview and observation methods. Based on the results of research conducted that the supporting factors of student interest in SMK 1 Bukittinggi City are influenced by internal or external factors and external factors.